Highly Entangled, Mechanically Robust Hydrogel Thin Films for Passive Cooling Materials via Open-Vessel Fabrication - Lihan Rong; Jiajiang Xie; Shigao Zhou; Tianqi Guan; Xinyi Fan; Wenjie Zhi; Rui Zhou; Feng Li; Yuyan Liu; Tingting Tang; Xiang Chen; Liyuan Zhang (Gels, 2025)
The scalable fabrication of hydrogels with high toughness and low hysteresis is critically hindered by oxygen inhibition, which typically produces brittle, highly crosslinked (HC) networks. This study presents an oxygen-tolerant photoinduced electron transfer–reversible addition–fragmentation chain transfer (PET-RAFT) strategy for synthesizing highly entangled (HE) polyacrylamide hydrogels under open-vessel conditions. By optimizing the water-to-monomer ratio (W = 3.9) and introducing lithium chloride (LiCl) for spatial confinement, we achieved a fundamental shift in mechanical performance. The optimized HE hydrogel exhibited a fracture energy of 1.39 MJ/m3 and a fracture strain of ~900%, starkly contrasting the brittle failure of the HC control (W = 20, C = 10−2) at ~50% strain. This represents an order-of-magnitude improvement in deformability. Furthermore, the incorporation of 15 wt% LiCl amplified the HE hydrogel’s fracture energy to 2.17 MJ/m3 while maintaining its low hysteresis. This method enables the rapid, scalable production of robust, transparent thin films that exhibit dual passive cooling via radiative emission (>89% emissivity) and evaporation, rapid self-healing, and reliable strain sensing at temperatures as low as −20 °C. The synergy of entanglement design and confinement engineering establishes a versatile platform for manufacturing multifunctional hydrogels that vastly outperform their crosslink-dominated predecessors.